Entrepreneurship policy in Brazil: its focus and gaps. (2018) - Borges, Cândido; Bezerra, Éder Danilo; Silva, Glessia; Andreassi, Tales; Ferreira, Vicente Da Rocha
This article presents an overview of public entrepreneurship policies in Brazil, and categorises them according to a model with eight types of entrepreneurship policy. In doing so, documents on public entrepreneurship policies on the websites of the 39 ministries, departments and agencies of the federal government were consulted. The results showed that public entrepreneurship policies in Brazil focus more on maintaining existing businesses, with finance policies and support for entrepreneurial, technological and innovation policies. However, few policies directly contribute to increasing the number of entrepreneurs in Brazil. These would include policies for the reduction of entry and exit barriers and policies on improving public infrastructure. It was also found that there are few policies on the promotion of entrepreneurship culture and education, which are essential if entrepreneurship is to be seen by more people as a career option.